ChemInform Abstract: L‐Proline Catalyzed Multicomponent Reactions: Facile Access to 2H‐Benzo[g]pyrazolo[3, 4‐b]quinoline‐5, 10(4H, 11H)‐dione Derivatives. Issue 48 (2nd December 2014) - Karamthulla, Shaik; Pal, Suman; Parvin, Tasneem; Choudhury, Lokman H.
Abstract 16 Title compounds of type (IV) are prepared using L‐proline as catalyst.